2021
DOI: 10.1183/16000617.0105-2021
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender in interstitial lung diseases

Abstract: Sex and gender differences influence key domains of research, lung health, healthcare access and healthcare delivery. In interstitial lung diseases (ILDs), mouse models of pulmonary fibrosis are clearly influenced by sex hormones. Additionally, short telomeres, a biomarker of telomere regulation gene mutations, are impacted by sex, while heritability unexplained by genetic variation may be attributable to gendered environmental factors that drive epigenetic control. Diseases like idiopathic pulmonary fibrosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 125 publications
(125 reference statements)
2
15
0
Order By: Relevance
“…While a relatively gender‐balanced prevalence emerges in HP, it may differ by gender, particularly as exposure to certain etiologic antigens in occupational HP may be gender‐based. Men appear to be more likely than women to develop HP due to exposure to agricultural and metalworking fluids 14 . In our study, the mean age of the patients diagnosed with HP was 49.36 ± 14.0 years, and the minimum age of diagnosis was 20, and the highest age of diagnosis was 76.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…While a relatively gender‐balanced prevalence emerges in HP, it may differ by gender, particularly as exposure to certain etiologic antigens in occupational HP may be gender‐based. Men appear to be more likely than women to develop HP due to exposure to agricultural and metalworking fluids 14 . In our study, the mean age of the patients diagnosed with HP was 49.36 ± 14.0 years, and the minimum age of diagnosis was 20, and the highest age of diagnosis was 76.…”
Section: Discussionmentioning
confidence: 46%
“…Men appear to be more likely than women to develop HP due to exposure to agricultural and metalworking fluids. 14 In our study, the mean age of the patients diagnosed with HP was 49.36 ± 14.0 years, and the minimum age of diagnosis was 20, and the highest age of diagnosis was 76. In the study of Kumar et al 15 in India with 103 HP patients, the mean age was found to be 47 ± 12.8 years, and it was found to be similar to our study.…”
Section: Discussionmentioning
confidence: 51%
“…We also aimed to limit the number of experimental visits considering patients' frailty and mobility issues. Although a male-predominant disease, our male-to-female ratio may not be representative of the general f-ILD population (53). For practical reasons (patients' availability in a small clinical center), sex was not considered a covariate in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings suggest that these expression differences may underlie the observed sex differences in pulmonary disease prevalence and severity. Human males are at higher risk for severe COVID-19 disease ( Scully et al., 2020 ; Takahashi et al., 2020 ), and males also experience greater prevalence and severity of interstitial lung disease and pulmonary fibrosis ( Kawano-Dourado et al., 2021 ). Intriguingly, these pathologies are increasingly recognized as being driven by defects in the lung epithelium, primarily AT2 cells ( Camelo et al., 2014 ; Katzen and Beers, 2020 ; Parimon et al., 2020 ), reinforcing the relevance of the AT2 transcriptomic differences between the sexes.…”
Section: Discussionmentioning
confidence: 99%